Fat - Lupton, Deborah (Short cuts, 2013)
4e de couv.: In contemporary western societies the fat body has become a focus of stigmatizing discourses and practices aimed at disciplining, regulating and containing it. Despite the fact that in many western countries fat bodies outnumber those that are thin, fat people are still socially marginalized and treated with derision and even repulsion. Medical and public health experts insist that an ‘obesity epidemic’ exists and that fatness is a pathological condition which should be prevented and controlled. Fat is a book about why the fat body has become so reviled and viewed as diseased, the target of such intense discussion and debate about ways to reduce its size down to socially and medically acceptable dimensions. It is also about the lived experience of fat embodiment: how does it feel to be fat in a fat-phobic society? Deborah Lupton explores fat as a cultural artefact: a bodily substance or body shape that is given meaning by complex and shifting systems of ideas, practices, emotions, material objects and interpersonal relationships. Fat reviews current scholarship and research into obesity discourse and politics, drawing upon critical perspectives offered in the humanities and social sciences and by fat activism and the size acceptance movement. It will be an engaging introduction for the interested general reader, as well as for students across the humanities and social sciences.
Keywords: approches et analyses; corps; cours; discipline; discours dominant; grossophobie; lit4700; premier cycle; santé; sciences humaines; sociologie; systèmes d'oppressions; thématiques; études culturelles